Variation in coverage by ethnic group of neonatal (Guthrie) screening programme in south London. - Streetly, A. (BMJ Group, 1994)
OBJECTIVES--To determine whether coverage of the neonatal (Guthrie) screening programme in Britain is different for groups at highest risk of sickle cell disease and to identify possible reasons for incomplete coverage. DESIGN--Descriptive study of coverage of screening programme and its variation by mobility, district of residence, and ethnic group. SUBJECTS--1727 infants born between 1 October and 31 December 1991. SETTING--Former West Lambeth and Camberwell District Health Authorities, London. MAIN OUTCOME MEASURE--Proportion of infants with an identifiable screening test result. RESULTS--Screening covered 1663/1727 (96.3%) infants overall (745/786 (94.8%) in West Lambeth; 918/941 (97.6%) in Camberwell). The relative odds ratio of an African infant not having been tested compared with a white infant was 3.05 (95% confidence interval 1.30 to 7.14) (2.08 (0.86 to 5.01) after adjustment for mobility and district of residence). For infants whose families moved into the districts after the birth compared with those born and resident in the districts the relative odds ratio of having been tested was 10.16 (4.85 to 21.29). The odds ratio of locally delivered infants in West Lambeth not having been tested compared with those in Camberwell was 2.12 (1.08 to 4.16) after adjustment for ethnic group. CONCLUSION--Coverage of the screening programme is incomplete and poorer in infants of African ethnic group than in white infants. Poorer coverage is also associated with mobility of the family around the time of birth. The findings have implications for using the neonatal programme for testing for sickle cell disease and other disorders. Arrangements for monitoring the existing screening programme are inadequate and an improved system should be established, similar to the scheme that monitors the immunisation programme.